Factors of Premature Rupture of Membranes: Systematic Literature Review - Nawangsari, Harnanik; Puspitasari, Maharnani Tri; Yuliasari, Yuliasari; Aticeh, Aticeh (Global Health Science Group, 2025)
The condition of premature rupture of membranes (PROM) is when the amniotic membrane ruptures before the labor stage. PROM remains known to be a material disease as a definite cause does not yet exist, but there are some suspicious internal or external circumstances associated with this condition.Complications of premature rupture of membranes (PROM) include complications in labor and puerperium, prolonged parturition, and an increase in the number of obstetric surgeries performed. Internal causes of PROM include parity, maternal age, cervical incompetence, polyhydramnios, and fetal presentation.Worldwide, PROM is 1.3%, with 8-10% of aterm pregnant women experiencing it in stable condition.Objective: Identify factors that increase the likelihood of premature rupture of membranes during pregnancy.Methods: This observation is based on a literature review of articles published in national and international journals. This article was published in 2020-2024 to ensure the information obtained is actual. Two databases that can be used to conduct article searches are PubMed and Google Scholar from 15 articles. By providing a summary of the discussion, it aims to improve understanding of the topic.This method can provide information about reality and literary analysis and insights, which allows for a good and relevant summary of the society to compare the results presented in the article. Results: Five national and five international articles found that parity, history of PROM, maternal age, gestational distance, anemia, employment status, infection, smoke exposure, and smoking behavior were risk factors for PROM. Some articles also found pregnancy, hereditary history, pregnancy status, fetal location, uterus, and gestational age.